Successful Management of Recurrent Subacute Thyroiditis by Adding Colchicine to Glucocorticoid Treatment: A Case Series Study - Tian, Zhenhua; Su, Yu; Zhang, Meijie; Zhang, Xiujuan; Guan, Qingbo (Hormone and Metabolic Research, 2020)
Although subacute thyroiditis (SAT) is thought to be a self-limited inflammatory thyroid disease, the recurrence rate of SAT is approximately 10–20%. It is difficult for these patients to stop glucocorticoid treatment, and they are usually bothered with recurrent pain and the side effects of glucocorticoids for more than several months. We describe three cases who were diagnosed with recurrent subacute thyroiditis after a reduction in prednisolone (PSL) dose, either immediately upon the cessation of PSL or shortly thereafter. Their symptoms, including the adverse effects of PSL, severely impacted their quality of life. After a complete assessment, we administered colchicine at 1 mg per day for 1–2 months to control the recurrence of SAT and monitored their routine blood parameters every two weeks. All 3 patients were successfully tapered off of PSL treatment and were free of frequently recurrent SAT. Colchicine may be therapeutic in patients with prednisolone-refractory, recurrent SAT. However, a large-scale, double-blind, controlled, prospective multicenter study is required to provide a solid body of evidence.
Keywords: recurrent subacute thyroiditis; SAT; management; colchicine; glucocorticoid